2020
DOI: 10.1161/atvbaha.119.313775
|View full text |Cite
|
Sign up to set email alerts
|

Drug Targeting of Plasminogen Activator Inhibitor-1 Inhibits Metabolic Dysfunction and Atherosclerosis in a Murine Model of Metabolic Syndrome

Abstract: Objective: Enhanced expression of PAI-1 (plasminogen activator inhibitor-1) has been implicated in atherosclerosis formation in humans with obesity and metabolic syndrome. However, little is known about the effects of pharmacological targeting of PAI-1 on atherogenesis. This study examined the effects of pharmacological PAI-1 inhibition on atherosclerosis formation in a murine model of obesity and metabolic syndrome. Approach and Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 73 publications
0
22
0
Order By: Relevance
“…Through local inhibition of plasmin generation, PAI-1 can reduce tissue remodeling and potentially stabilize the fibrin matrix of the developing plaque. Furthermore, studies on the effects of pharmacological PAI-1 inhibition on atherogenesis in mice with obesity and metabolic syndrome also suggested a role for PAI-1 in adipose tissue inflammation, macrophage accumulation, and inducing senescence of smooth muscle cells through its interaction with LRP1 [ 49 ]. Whereas several studies demonstrated substantial evidence for PAI-1 as an independent risk factor for CVD including myocardial infarction and stroke [ 50 , 51 , 52 ], coronary heart disease [ 53 ], venous thrombosis [ 54 ], and atherosclerosis [ 45 , 55 ], other studies could not confirm these associations or the significance for the link was lost after adjusting for other risk factors, such as age, sex, and metabolic abnormities [ 52 , 56 , 57 , 58 ].…”
Section: Role Of Pai-1 In Diverse Pathologiesmentioning
confidence: 99%
“…Through local inhibition of plasmin generation, PAI-1 can reduce tissue remodeling and potentially stabilize the fibrin matrix of the developing plaque. Furthermore, studies on the effects of pharmacological PAI-1 inhibition on atherogenesis in mice with obesity and metabolic syndrome also suggested a role for PAI-1 in adipose tissue inflammation, macrophage accumulation, and inducing senescence of smooth muscle cells through its interaction with LRP1 [ 49 ]. Whereas several studies demonstrated substantial evidence for PAI-1 as an independent risk factor for CVD including myocardial infarction and stroke [ 50 , 51 , 52 ], coronary heart disease [ 53 ], venous thrombosis [ 54 ], and atherosclerosis [ 45 , 55 ], other studies could not confirm these associations or the significance for the link was lost after adjusting for other risk factors, such as age, sex, and metabolic abnormities [ 52 , 56 , 57 , 58 ].…”
Section: Role Of Pai-1 In Diverse Pathologiesmentioning
confidence: 99%
“…The investigation of PAI-1 is relevant for clinical application to various disease states [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. PAI-1 levels are elevated in several diseases states and, in rodent models, the ablation/inhibition of PAI-1 tissue repair [ 27 , 28 , 126 , 132 ] whereas deficiency in Plau or other components of the plasminogen system has the opposite effect [ 28 , 35 , 37 , 38 , 40 ].…”
Section: Therapeutic Interventions To Normalize Pai-1mentioning
confidence: 99%
“…Most notable of these inhibitors include tiplaxtinin (PAI-039) and the three generations of TM-related drugs (TM5001, TM5009, TM5275, TM5441, TM5509, and TM5614). These inhibitors have been studied in pathological conditions including cancer, cardiovascular disease, pulmonary fibrosis renal diseases, liver diseases and others [ 17 , 22 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 71 ]. Most if not all of these inhibitors have been shown to bind the active RCL domain on PAI-1 in a reversible manner to ultimately abolish its ability to bind tPA/uPA [ 16 , 69 , 70 ].…”
Section: Therapeutic Interventions To Normalize Pai-1mentioning
confidence: 99%
See 2 more Smart Citations